DIMERISATION OF THE SECONDARY METABOLITES OF TEPHROSIA VOGELII AS A POTENTIAL MOLECULAR SWITCH - Hendson Limawan, Deryl
Molecular switches are a type of molecular machine that can have two or more stable configurations, thus can be used to control two or more reversible conditions. One of the molecular switch systems that is currently being widely developed is the photochromic molecular switch, whose configurational changes can be induced by light. The total synthesis of molecular switches with specific structures generally requires a long and expensive process due to the numerous synthesis steps involved. In this research, the utilization of Indonesian natural compounds, namely secondary metabolites isolated from Tephrosia vogelii such as isolonchocarpin, 7-methoxy-8-prenylflavanone, pongachin, deguelin, and tephrosin, is proposed. The synthesis of molecular switches from these secondary metabolites was carried out using the McMurry coupling reaction, which is a reaction for olefin formation through the reductive coupling of carbonyl compounds on the substrate utilizing a low-valence titanium catalyst. In the isolation stage of this research, 708.1 mg of isolonkokarpin (1), 227.5 mg of 7-methoxy-8-prenylflavanone (2), 377.1 mg of tephrosin (3), 233.1 mg of pongacin (4), and 139.8 mg of deguelin (5) were successfully obtained. The McMurry reaction on compounds 1 and 2 successfully formed the E-D1 and E-D2 dimers with 53% and 48.5% yield respectively. Meanwhile, the McMurry reaction on 3 and 5 both produced a reduced product D3 with 30.5% and 24.2% yield respectively. The McMurry reaction on 4 produced a mixture of products suspected to contain D4. Photoirradiation tests on E-D1 and E-D2 at 395 nm were suspected to cause dimer photoisomerization and form Z-D1 and Z-D2 species, while photoirradiation at 365 nm was suspected to cause photoisomerization followed by dimer photocyclization, and photoirradiation at 254 nm was suspected to cause dimer photodegradation. The attempt to induce back-photoisomerization of compounds Z-D1 and Z-D2 using monochromatic visible light at 450 nm, 520 nm, and 635 nm, as well as white light from fluorescent and LED lamps, has not yet been successful. Therefore, it is shown that an overcrowded alkene framework has been successfully synthesized from natural compounds of Indonesian origin through a one?step reaction. Despite the lack of reversibility, this framework demonstrates controlled E ? Z photoisomerization, suggesting its potential for further development into molecular switch compounds